Inhaled foreign bodies in laryngectomees - Kishore, A. (Springer India, 2001)
As a consequences of laryngectomy, patients possess a tracheostoma presenting on the neck skin which is an intrinsic component of their airway and which provides a portal through which potentially dangerous foreign bodies can enter the tracheobronchial tree. In addition, new methods of speech rehabilitation require the placement of a valve within the stoma which needs regular cleaning and manipulation. We report 3 cases of aspiration, each of a different piece of equipment that is commonly associated with laryngectomees, illustrating potential unique risks to the airway in such individuals.